Management of oral anticoagulant therapy after intracranial hemorrhage in patients with atrial fibrillation - Lucà, Fabiana; Colivicchi, Furio; Oliva, Fabrizio; Abrignani, Maurizio; Caretta, Giorgio; Di Fusco, Stefania Angela; Giubilato, Simona; Cornara, Stefano; Di Nora, Concetta; Pozzi, Andrea; Di Matteo, Irene; Pilleri, Anna; et al. (Frontiers in Cardiovascular Medicine, 2023)
Intracranial hemorrhage (ICH) is a potentially severe complication of oral anticoagulants (OACs) and antiplatelet therapy (APT). Patients with atrial fibrillation (AF) who survived ICH present both an increased ischemic and bleeding risk. Due to its lethality, initiating or reinitiating OACs in ICH survivors with AF is challenging. Since ICH recurrence may be life-threatening, patients who experience an ICH are often not treated with OACs, and thus remain at a higher risk of thromboembolic events. A point worth mentioning is that patients with a concomitant recent ICH and AF have been excluded or are poorly represented in randomized controlled trials (RCTs) on ischemic stroke risk management in AF. Nevertheless, observational studies showed that in AF patients who survived ICH, ischemic stroke and mortality rates were significantly lower among those treated with OACs. However, the risk of hemorrhagic events, including recurrent ICH, was not necessarily increased, especially in patients with post-traumatic ICH. The optimal timing of anticoagulation initiation or restarting after an ICH in AF patients is also largely debated. Finally, the left atrial appendage occlusion option should be evaluated in AF patients at a very high risk of recurrent ICH. Overall, a multidisciplinary team composed of cardiologists, neurologists, neuroradiologists, neurosurgeons, patients, and their families should be involved in management decisions. According to available evidence, this review outlines the most appropriate anticoagulation strategies after an ICH that should be adopted to treat this neglected subset of patients.